Rodenticide Comparative Effect of Klerat® and Zinc Phosphide for Controlling Zoonotic Cutaneous Leishmaniasis in Central Iran - Arshad VEYSI (Iranian Journal of Parasitology, 2016)
Background: Zoonotic cutaneous leishmaniasis (ZCL) is a neglected disease with public health importance that is common in many rural areas of Iran. In recent years, behavioral resistance and/or bait shyness against the common rodenticide among reservoir hosts of ZCL have been reported. The aim of this study was to evaluate the effectiveness of Klerat® and zinc phosphide against natural reservoir of ZCL.